PENDAMPINGAN LANSIA MELALUI KEGIATAN SENAM LANSIA SEBAGAI UPAYA PENINGKATAN KESEHATAN FISIK DAN PSIKIS LANSIA DI POSYANDU RT 01 DAN RT 02 KELURAHAN LINGKAR SELATAN KECAMATAN PAAL MERAH TAHUN 2020 - Dwi Noerjoedianto; Arnild Augina Mekarisce; Risty Ivanti; Willia Novita Eka Rini; Fitria Eka Putri (Jurnal Salam Sehat Masyarakat (JSSM), 2020)
Elderly is a period when organisms have reached their prime in size, function, and some have shown their decline over time. Based on the indicators of physical fitness in the elderly in Indonesia, it is still lacking, this is proven by the high morbidity rate in the elderly. To be able to face the elderly who can enjoy their life and maintain their strength and fitness, the elderly must do regular sports activities, carry out a healthy lifestyle, take a break from smoking and have health checks. This community service aims to improve the physical and psychological health of the elderly through exercise assistance activities for the elderly. This activity is in partnership with RT 01 and RT 02 Kelurahan Lingkar Selatan, Paal Merah District. This activity involves all elderly who are registered in the posyandu as a target of improving physical and psychological health through elderly exercise. Activities are carried out from compiling an activity plan to monitoring and evaluating activities according to the set targets and outputs. The results of the pre-test and post-test activities, which consisted of four indicators of evaluation, had increased, but this was not too significant because this activity only took place during service activities, to find maximum results, it was necessary to sustain the activity. Increased knowledge of the RT elderly group. 01 and RT. 02 Kelurahan Lingkar Selatan on the importance of Lansi Gymnastics in maintaining physical and psychiatric health and Increasing awareness and skills of the elderly group RT. 01 and RT. 02 Lingkar Selatan Village in doing elderly gymnasticsArtikel